Marcher with "Hi Mom" sign - Sahl, Ted (photographer):::Creator::::::::::::
Woman marcher holds a sign that reads, "Hi Mom" during the National March on Washington for Lesbian and Gay Rights. A sign in the background reads, "An army of lovers c[an]not fail!"